2012
DOI: 10.1371/journal.pone.0048424
|View full text |Cite
|
Sign up to set email alerts
|

A Cancer Vaccine Induces Expansion of NY-ESO-1-Specific Regulatory T Cells in Patients with Advanced Melanoma

Abstract: Cancer vaccines are designed to expand tumor antigen-specific T cells with effector function. However, they may also inadvertently expand regulatory T cells (Treg), which could seriously hamper clinical efficacy. To address this possibility, we developed a novel assay to detect antigen-specific Treg based on down-regulation of surface CD3 following TCR engagement, and used this approach to screen for Treg specific to the NY-ESO-1 tumor antigen in melanoma patients treated with the NY-ESO-1/ISCOMATRIXTM cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 43 publications
2
43
0
Order By: Relevance
“…Immunotherapies that enhance antigenspecific Treg expansion and suppressive function delayed multi-cytokine-producing Teff activation, resulting in disease control (41,42). To date, the relationship between antigenspecific Teffs and Tregs has not been examined in detail in cancer, although some in vitro and observational reports exist [19][20][21]. Our study extends the knowledge base gained from previous investigations by comparing a large panel of adjuvants for their ability to modulate the vaccine-specific Teff: Treg balance.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Immunotherapies that enhance antigenspecific Treg expansion and suppressive function delayed multi-cytokine-producing Teff activation, resulting in disease control (41,42). To date, the relationship between antigenspecific Teffs and Tregs has not been examined in detail in cancer, although some in vitro and observational reports exist [19][20][21]. Our study extends the knowledge base gained from previous investigations by comparing a large panel of adjuvants for their ability to modulate the vaccine-specific Teff: Treg balance.…”
Section: Discussionsupporting
confidence: 53%
“…These Tregs were shown to suppress proliferation of Teffs in an antigen-specific manner when cultured with tumor peptide-loaded dendritic cells (19). In a clinical study of patients with melanoma immunized with NY-ESO-1 protein in ISCOMATRIX, vaccination increased the frequency of NY-ESO-1-specific Tregs in peripheral blood mononuclear cells (PBMC) and tumor tissue (20). We have shown that therapeutic vaccination of patients with melanoma with Melan-A peptide plus CpG-ODN in Montanide results in robust expansion of Melan-A-specific CD8 þ T cells within PBMCs with a concomitant decrease in Melan-A-specific Tregs (1,2,21).…”
Section: Introductionmentioning
confidence: 99%
“…In our (18,19). These studies, however, did not use ex vivo assessments by tetramers, but indirect strategies that may have confounded results and conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…Strategies employing the treatment of cancer cells with demethylating agents as well as histone demethylase inhibitors to reactivate or increase the expression of the CTA genes including NY-ESO-1 have previously been published in glioma, myeloid leukemia, and melanoma (17)(18)(19)(20). Clinical trials are now underway using NY-ESO-1 targeted immunotherapeutic strategies that include use of genetically engineered T-cells transduced with NY-ESO-1-T-cell receptors (TCRs) directly targeting melanoma cells (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%